Results of Analysis of the State of Development of the Intelligent Microclimate Management System of the Smart Greenhouse (Global Scientific Review, 2022)
Nowadays, the importance of performing research through an IoT project is increasing for their practical implementation in agriculture: both on an industrial scale and for individual use. The article discusses the possibilities and advantages of the IoT project for growing plants, which arouses high interest among extremely busy residents of city apartments who grow seedlings for their garden or just ornamental plants for beauty and comfort in the house. The research results were obtained by performing a master's work on the theoretical implementation and practical operation of IoT elements. The interest of the presented results lies in the novelty of integrating the process of caring for their crops into the user's daily life: now the results of their work can be shared on social networks (in the form of video materials on monitoring the harvest). This approach makes this ICT and IoT project very attractive to a young audience, working in agriculture.